Endoglycan Regulates Purkinje Cell Migration by Balancing Cell-Cell Adhesion - Baeriswyl, Thomas; Schaettin, Martina; Leoni, Simone; Dumoulin, Alexandre; Stoeckli, Esther T. (Frontiers in Neuroscience, 2022)
The importance of cell adhesion molecules for the development of the nervous system has been recognized many decades ago. Functional in vitro and in vivo studies demonstrated a role of cell adhesion molecules in cell migration, axon growth and guidance, as well as synaptogenesis. Clearly, cell adhesion molecules have to be more than static glue making cells stick together. During axon guidance, cell adhesion molecules have been shown to act as pathway selectors but also as a means to prevent axons going astray by bundling or fasciculating axons. We identified Endoglycan as a negative regulator of cell-cell adhesion during commissural axon guidance across the midline. The presence of Endoglycan allowed commissural growth cones to smoothly navigate the floor-plate area. In the absence of Endoglycan, axons failed to exit the floor plate and turn rostrally. These observations are in line with the idea of Endoglycan acting as a lubricant, as its presence was important, but it did not matter whether Endoglycan was provided by the growth cone or the floor-plate cells. Here, we expand on these observations by demonstrating a role of Endoglycan during cell migration. In the developing cerebellum, Endoglycan was expressed by Purkinje cells during their migration from the ventricular zone to the periphery. In the absence of Endoglycan, Purkinje cells failed to migrate and, as a consequence, cerebellar morphology was strongly affected. Cerebellar folds failed to form and grow, consistent with earlier observations on a role of Purkinje cells as Shh deliverers to trigger granule cell proliferation.